COMPRESSION STRENGTH, HEAT DEGRADATION AND UL-94 FLAMMABILITY PROPERTIES OF POLYURETHANE FILLED BENTONITE COMPOSITE FOAMS - Razak, J.A.; Mohamad, M.; Puspitasari, P.; Flaifel, M.H.; Mohamad, N. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
This study has reported the potential of bentonite mineral clay as filler, to improve the resulted properties of polyurethane (PU) based composite foams. Bentonite was incorporated into PU formulation, through high-speed mechanical stirring process and has been reacted at 1:1.4 ratio of polyols and isocyanate. The effects of bentonite addition at various loadings (0 – 5.00 wt. %) has been evaluated in-terms of their compression strength and fracture toughness behavior, the fracture morphology, heat degradation and UL-94 flammability properties. From this work, it was found that, at lower addition of bentonite filler (0.50 wt. %), the compression strength had improved about 77%, while heat degradation characteristic of PU/bentonite composite was significantly enhanced at higher bentonite loading. It was also proven that the added bentonite mineral clay filler is actually able to retard the fire, due to their extinguishing characteristics. Hence, related flammability mechanism of PU/bentonite composite foams has been suggested. Addition of bentonite mineral clay filler into PU gives benefits to the mechanical strength, heat and flammability properties of PU/bentonite composite foams, at different filler loadings variation. This, would solve several issues related to lower mechanical strength, limited fire behavior and worst heat resistance characteristics of unfilled PU foam system.